Feeding Efficiency of Green Lacewing, Chrysoperla carnea (Stephens) against Different Species of Aphid in Laboratory Conditions - Rana, Lok Bahadur; Mainali, Ram Prasad; Regmi, Homan; RajBhandari, Binayak Prasad (International Journal of Applied Sciences and Biotechnology, 2017)
Green lacewing, Chrysoperla carnea Stephens (Neuroptera: Chrysopidae) is the most effective polyphagous predator of different species of aphids and is commonly known as “aphid lion” . The experiment on feeding efficiency of green lacewing was studied in the laboratory of Entomology Division, NARC, Khumaltar, Lalitpur, Nepal from 21st , December 2015 to 26th, March 2016. The known number of predatory larva of green lacewings were fed with known number of seven different species of live aphid and frozen Corcyra eggs representing each treatment. The treatments were replicated four times. The predatory efficiency was calculated by counting the number of consumed host per day. The result revealed that the predatory efficiency of C. carnea larvae were increased from first to third instar and third instar were more voracious as compare to first two instars. It consumed significantly the highest rice moth, Corcyra cephalonica followed by Aphis craccivora and others aphid species, respectively. From this experiment, it is evident that the green lacewing is potent bio-agent against different aphid species and hence further research is required simultaneously in the farmer’s field conditions.Int. J. Appl. Sci. Biotechnol. Vol 5(1): 37-41